Pengaruh Store Atmosphere dan Sales Promotion terhadap Keputusan Pembelian Studi pada Konsumen ACE Hardware Indonesia, TBK. Cabang Technomart Karawang - Firly Novia; Puji Isyanto; Asep Darojatul Romli (J-MAS (Jurnal Manajemen dan Sains), 2023)
The development of times, technology, and lifestyles that make people demand more convenience in shopping. Changes in shopping patterns are also influenced by influencing factors, namely the shopping location environment. Ace hardware is a retail company that sells all the most complete home and lifestyle equipment in Indonesia that answers all people's needs in creating beauty in a house. Ace hardware is a retail store that is very concerned about the comfortable atmosphere when shopping and provides an attractive offer, namely by having promotions given to the community with the aim of increasing purchasing decisions for the community through the efforts and strategies that have been made. In this study the authors used a quantitative descriptive method based on multiple linear regression analysis. The results of this study indicate that all hypotheses, Store Atmosphere and Sales Promotion have a significant and positive effect on purchasing decisions. Studies on Consumers Ace Hardware Indonesia, Tbk. Technomart Karawang Branch. However, if without Store Atmosphere and Sales Promotion or the two independent variables are not implemented, there will be a decrease in purchasing decisions and consumers will switch to other competitors. Conversely, if the store atmosphere and sales promotion are implemented all the independent variables can increase purchasing decisions at Ace Hardware Indonesia, Tbk. technomart karawang Branch.